Kinetics of Ammonia Biodegradation Using EM4 with Palm Sugar as an External Carbon Source - Denanda Clarasati Puteri; Rizky Ibnufaatih Arvianto; Suhirman Suhirman; Adna Ivan Ardian; Muhamad Iqbal Putra; Muhammad Zulfikar Luthfi; Ihsan Wiratama; Jerry Jerry; Dennis Farina Nury (Universitas Nusa Cendana, 2026)
Biological treatment of ammonia requires sufficient carbon availability to maintain stable microbial activity and sustain optimal degradation rates. This study evaluates the kinetics of ammonia biodegradation using an EM4 microbial consortium supplemented with palm sugar as an external carbon source in aerobic batch reactors. Initial ammonia concentrations of 10, 30, and 50 ppm were evaluated over six days of operation. Monitored parameters included ammonia concentration, pH, and biomass (MLSS), while kinetic evaluation applied a pseudo–first‑order model via the ln(St/S0)–time relationship. The results showed removal efficiencies of 79.0–83.4%, accompanied by MLSS increases from 2,000 to 4,600 mg/L with higher initial concentrations. The pH range of 5.8–8.5 remained conducive to microbial activity. The ln(St/S0) curves exhibited strong linearity, confirming the suitability of the pseudo–first‑order model, and the reaction rate constants increased under higher substrate and biomass conditions. These findings indicate that palm sugar is effective as an external carbon source for sustaining process stability and accelerating ammonia removal. The integration of EM4 with a natural carbon source demonstrates potential as an efficient, economical, and readily implementable biological approach for ammonia treatment in wastewater.